Diritto e tecnologia: una riflessione critica sui contenuti di un rapporto in continua evoluzione - Vestoso, Margherita (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The work reviews “Diritto e tecnologie informatiche. Questioni di informatica giuridica, prospettive istituzionali e sfide sociali”, a book edited by Thomas Casadei and Stefano Pietropaoli, offering insights on how digital society has transformed the relationship between law and technology. Resulting from an interesting interdisciplinary reflection, the essays presented in the book try to shed light, in particular, on the numerous and complex issues that cross such a scenario which is partly still unexplored. Our work aims to sketch, in its essential features, the path traced by these reflections, taking into account the plurality of the themes dealt with, the different angles, and the numerous points of contact that put the same topics in close communication with one another.